A RATIONAL SCHEME OF MASTERING THE CARRIAGE DURING THE INTRODUCTION OF HIGH-SPEED TRAINS ON ONE OF THE PARALLEL RAILWAY LINES - Kurhan, M. B.; Zaiats, M. A. (Science and Transport Progress, 2006)
The authors have developed a method of forming a ratoinal scheme of stage-by-stage integration of services on parallel-bound railroad directions, when high-speed services are introduced on one of them.